Sistem Pemantauan Detak Jantung Berbasis ESP32 Menggunakan Sensor AK90 Dengan Antarmuka Web - Chalik, Aqsa; Rohman, Hidayatul; Rosdiansyah, Luthfia; Fazrian, Alief; Hidayat, Hidayat (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Heart rate monitoring plays a crucial role in maintaining cardiovascular health, enabling early detection of disorders such as arrhythmia. This study aims to develop an Internet of Things (IoT)-based heart rate monitoring system using the AK90 sensor and ESP32 microcontroller integrated with a web interface to support real-time monitoring and digital data storage. The system was developed using the Waterfall approach, consisting of requirement analysis, system design, implementation, testing, and deployment in a Posyandu environment. The AK90 sensor utilizes the principle of photoplethysmography to detect heart rate, with data processed by the ESP32, displayed on an OLED screen, and stored via a local web server. Testing on four subjects showed that the system was able to record heart rates within the normal range (60–100 BPM) after a 10-second sensor stabilization period, although initial readings often showed a value of 0 due to the initialization process. This system offers a practical, affordable, and standalone solution for heart health monitoring, with potential for future enhancements such as notifications and historical data analysis to support medical diagnosis.